MARKETING SKILL ADAPTIF DAN PEMANFAATAN APLIKASI DIGITAL SEBAGAI PILAR UTAMA DALAM MENGHADAPI DINAMIKA PASAR MODERN - Muhammad Sawal Pitriyadi; Zuhrinal M Nawawi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study examines the integration of business writing skills and marketing skills as an effort to enhance communication strategies in modern marketing practices. In the era of digital transformation, companies are required to adapt to the latest technological developments, and the ability to communicate effectively through written content has become increasingly important. This paper discusses the impact of business writing on marketing communication, the challenges of writing in the digital age, and the importance of writing skills in conveying messages clearly and persuasively. It also explores how marketing skills can be adapted to create effective communication strategies that are in line with digital marketing trends. Through this integration, companies can improve their marketing efforts, creating better engagement with customers and achieving marketing objectives more efficiently. The study concludes that mastering both business writing and marketing skills is crucial in improving communication strategies and enhancing the overall marketing performance in the digital age.